ANALYSIS OF PHYSICAL WORK ENVIRONMENT, NON-PHYSICAL WORK ENVIRONMENT, AND TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE OF COMOP 2 AND COMOP 3 AT PT X - Ahmad Syahrir Ridwan; Dimas Nugroho Dwi Seputro (Journal of Social and Economics Research, 2025)
PT X, as a national geotechnical consulting company, faces challenges in maintaining optimal employee performance in the COMOP 2 and COMOP 3 Departments. The emerging phenomenon is the fluctuation in productivity and work quality, which is suspected to be influenced by the physical work environment, non-physical work environment, and the leadership style applied. This study aims to examine the influence of the physical work environment, non-physical work environment, and transformational leadership on the performance of employees in COMOP 2 and COMOP 3 at PT X. The research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to employees in both departments. The sample consisted of 10 employees selected using purposive sampling. Data analysis was conducted using multiple linear regression with a significance level of 0,05. The results show that the physical work environment (X1) and non-physical work environment (X2) do not have a partial effect on employee performance (Y), while transformational leadership (X3) has a partial effect. Simultaneously, the independent variables do not have a significant effect. Approximately 41,1% of employee performance can be explained by these three variables.